Performance and Power Efficiency Analysis of the Symmetric Cryptograph on Two Stream Processor Architectures - Guang Xu; Hong An; Gu Liu; Ping Yao; Mu Xu; Wenting Han; Xiaoqiang Li; Xiurui Hao (2009 Fifth International Conference on Intelligent Information Hiding and Multimedia Signal Processing, 2009)
Multimedia and some scientific applications have achieved good performance on the stream processor architecture by employing the stream programming model. In order to find out the way to accelerate the symmetric cryptograph on stream processor, we implement and analyze cryptograph algorithms on different stream processors in this paper. Four cipher algorithms including RC5, AES, TWOFISH and 3DES in ECB model are implemented on three platforms, which are stream processor SPI Storm SP16-G160, NVIDIA GeForce 9800GTX, Intel Core2 dual-core processor E7300. The difference of architecture between two stream processors and the character of programming model are described. When we compare throughput rate of these applications, 9800GTX is shown with 4-30x performance improvement over E7300, SP16 achieves the highest power efficiency and obtains 15-20x increase over E7300 in Gops/Watt.